1998
DOI: 10.1002/pdi.1960150208
|View full text |Cite
|
Sign up to set email alerts
|

An audit of a comprehensive screening programme for diabetes in pregnancy

Abstract: Universal screening of gestational diabetes (GDM) has been advocated but is seldom practised in the United Kingdom. We report 12 months' audit of a comprehensive screening programme for women attending a teaching hospital for antenatal care. The population served is almost exclusively Caucasian. Of 4,016 women who booked in for delivery at the hospital, 3,3 16 (83%) completed the screening protocol. Sixty-seven women (1.7%) were found to have gestational diabetes after a 75 gram oral glucose tolerance test (OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The ADIPS recommends the 75 g OGTT at 6–12 weeks postnatal period, 12 and the UK NICE recommends a fasting plasma assessment; 13 however, the OGTT will also identify impaired glucose tolerance (2-hour postload sample ≥11.1 mmol/L) as well as impaired fasting glucose so may be preferred and the test that adequately identifies abnormal postnatal glucose metabolism and insulin resistance may depend on population characteristics. 38 , 39 However, rates of attendance at this postnatal assessment are low 40 , 41 and may reflect women’s perception of personal low risk as described earlier and also a lack of perceived importance placed on this condition by clinicians.…”
Section: Care Following Birthmentioning
confidence: 87%
“…The ADIPS recommends the 75 g OGTT at 6–12 weeks postnatal period, 12 and the UK NICE recommends a fasting plasma assessment; 13 however, the OGTT will also identify impaired glucose tolerance (2-hour postload sample ≥11.1 mmol/L) as well as impaired fasting glucose so may be preferred and the test that adequately identifies abnormal postnatal glucose metabolism and insulin resistance may depend on population characteristics. 38 , 39 However, rates of attendance at this postnatal assessment are low 40 , 41 and may reflect women’s perception of personal low risk as described earlier and also a lack of perceived importance placed on this condition by clinicians.…”
Section: Care Following Birthmentioning
confidence: 87%
“…We also identified three cohorts with IPD (the Atlantic DIP study, 59 Warwick/Coventry 60 and the BiB study 22 ), reporting GDM prevalence for a UK or Irish cohort. 42,44,118,[126][127][128][129][130][131][132][133][134] After data extraction, two publications 128,134 were excluded because they reported data from the same cohort. One additional paper (on the HAPO cohort 6 ) was included, having been identified for another review undertaken as part of this project (see Chapter 3).…”
Section: Resultsmentioning
confidence: 99%
“…This assumes that, conditional on diagnosis of GDM, the experience of having been risk factor screened prior to diagnosis influences uptake of further screening. Gregory et al 127 reported an uptake of follow-up for women with GDM who were identified with universal OGTT of 52%. For women who were previously screened by risk factors, a higher estimate of follow-up uptake was identified (83%) from a retrospective study 233 based on routine hospital data collected in Bradford.…”
Section: Uptake Ofmentioning
confidence: 99%
See 1 more Smart Citation